Entanglement witnessing in superconducting beamsplitters: letter - Soller, Henning; Hofstetter, Lukas; Reeb, David (epl, 2013)
We analyse a large class of superconducting beamsplitters for which the Bell parameter (CHSH violation) is a simple function of the spin detector efficiency. For these superconducting beamsplitters all necessary information to compute the Bell parameter can be obtained in Y-junction setups for the beamsplitter. Using the Bell parameter as an entanglement witness, we propose an experiment which allows to verify the presence of entanglement in Cooper pair splitters.
Published online 26 June 2013
Gesehen am 09.02.2022